2021
DOI: 10.3390/ijerph18020664
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Characteristics and Mood of Professional Esports Athletes: A Multi-National Study

Abstract: Esports is becoming increasingly professionalized, yet research on performance management is remarkably lacking. The present study aimed to investigate the sleep and mood of professional esports athletes. Participants were 17 professional esports athletes from South Korea (N = 8), Australia (N = 4), and the United States (N = 5) who played first person shooter games (mean age 20 ± 3.5 years, 100% male). All participants wore a wrist-activity monitor for 7–14 days and completed subjective sleep and mood questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 73 publications
(38 reference statements)
7
31
2
3
Order By: Relevance
“…The current results showed later sleep onset and sleep offset than what is normal among athletes in other traditional sports (Hrozanova et al, 2020 ). However, the results in the current study confirm results from a recent study among esport players that show both delayed sleep patterns and prolonged wake after sleep onset (Lee et al, 2021 ). A potential explanation might be that games are played among competitors in every global time zone, and hence also at night time.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The current results showed later sleep onset and sleep offset than what is normal among athletes in other traditional sports (Hrozanova et al, 2020 ). However, the results in the current study confirm results from a recent study among esport players that show both delayed sleep patterns and prolonged wake after sleep onset (Lee et al, 2021 ). A potential explanation might be that games are played among competitors in every global time zone, and hence also at night time.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study in a comparable sport such as chess and within the same age group reported shorter sleep time (6:44) (Moen et al, 2020 ). A recent study among professional esport players showed a median total sleep time of 6:48 h per night over a period of 7–14 days (Lee et al, 2021 ), and another study reported median total sleep time 7:26 h per night (Lee et al, 2020 ). Thus, the total sleep time among esport players seems to be 7 h per night ±15 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Different studies acknowledge the presence of sleep problems in esports players. [43][44][45] Competition, which might induce distress and anxiety, as previously stated, has been associated with sleep disturbance before competition 45 and prolonged sleep onset and offset times. 45 Coping strategies and alcohol consumption Poor mental health also seemed to be associated with alcohol consumption in athletes 42 and the general Portuguese population.…”
Section: Coping Strategies and Sleep Disturbancementioning
confidence: 78%
“…Although the MOBA game genres are played in a high-intensity situation, spectators can be gratified when playing and can escape from daily worries into the simulated competitive community. Since gameplay in a high-intensity situation typically causes longer playing time, which may lead to a higher depressed mood [34], the players of MOBA game genres might be attracted by the opportunity to release their tension. The action game genre features single-player experiences, and the actual action can provide an opportunity for viewers to let their minds wander.…”
Section: Discussionmentioning
confidence: 99%